Analysis of serotypes and pulsed field gel electrophoresis molecular type of Listeria monocytogenes in Fujian Province from 2000 to 2018 - Weiwei CHEN; Yingxiang ZHENG; Lingqing YE; Zehui CHEN; Huilong CHEN; Suzhen YE (Zhongguo shipin weisheng zazhi, 2020)
Objective To analyze the serotypes and molecular type of Listeria monocytogenes strains isolated from food, clinical case and environment in Fujian Province, so as to provide reference for the outbreak identification and traceability of foodborne diseases. Methods Using multiplex polymerase chain reaction (PCR) serotyping, immune serum agglutination and pulsed field gel electrophoresis (PFGE) to classify the strains. Results The 117 strains of Listeria monocytogenes strains were divided into 4 PCR serotypes, 67.5% (79/117) of which were 1/2a (3a), 23.1% (27/117) were 1/2b (3b), 5.1% (6/117) were 1/2c (3c) and 4.3% (5/117) were 4b (4d, 4e). Among the 9 strains isolated from cases, 6 strains were 1/2a, 2 strains were 4b and 1 strain was 1/2b. 117 Listeria monocytogenes strains were divided into 83 different PFGE types by Asc I restriction endonucleases, and 10 strains of which had unique and single types. Nine clinical case isolates were divided into 8 different PFGE types. Conclusion 1/2a serotype was dominant in Listeria monocytogenes isolated from food and clinical specimens in Fujian Province, and 4b serotype should be concerned.